`y1(x) = 3e^(2x)-7e^x`

Differentiating this would get,

`y'1(x) = 6e^(2x)-7e^x`

Differentitating again,

`y''1(x) = 12e^(2x) -7e^x`

`(d^2y1)/(dx^2) = 12e^(2x) -7e^x`

Following the same procedure for y2(x),

`y2(x) = e^(2x)+e^x`

Differentiating this would get,

`y'2(x) = 2e^(2x)+e^x`

Differentitating again,

`y''2(x) = 4e^(2x)+e^x`

`(d^2y2)/(dx^2) = 4e^(2x)+e^x`

Both these second order ODEs are of the form of,

`(d^2y)/(dx^2) = ae^(2x)+be^x`

**Therefore the required solution is,**

`(d^2y)/(dx^2) = ae^(2x)+be^x`

To find y3(x) we can integrate the above equations and find values for a and b.

Integrating wrt x,

`(dy)/(dx) = 1/2ae^(2x)+be^x`

But we know, y'3(0) = 0

Therefore,

`0= 1/2a+b`

a+2b = 0 ----1

Integrating again,

`y = 1/4ae^(2x)+be^x`

But y3(0) = 1

So,

`1= 1/4a+b`

a+4b = 4 ----2

solving equationf 1 and equation 2 will give,

a = -4 and b = 2

Therefore y3(x) is given by,

`y3(x) = 1/4(-4)e^(2x)+2e^x`

`y3(x) = -e^(2x)+2e^x`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.